Preoperative language mapping using navigated TMS compared with extra-operative direct cortical stimulation using intracranial electrodes: A case report. (March 2020) - Chowdhury, Fahmida A.; Caciagli, Lorenzo; Whatley, Benjamin P.; McLaughlin, Charlotte; Sanders, Brett; Wehner, Tim; Diehl, Beate
Highlights: rTMS provides a non-invasive means of performing pre-operative language mapping. Sensitivity and specificity in epilepsy patients is lower than reported in tumour surgery. Future methodological improvements may improve this.